2021
DOI: 10.1101/2021.08.05.455215
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coordinated Cross-Talk Between the Myc and Mlx Networks in Liver Regeneration and Neoplasia

Abstract: The Myc bHLH-ZIP transcription factor is deregulated by most cancers. As a heterodimer with the bHLH-ZIP protein Max, Myc regulates target genes that contribute to metabolism and proliferation. This “Myc Network” cross-talks with the “Mlx Network” comprised of the Myc-like bHLH-ZIP proteins MondoA and ChREBP and the Max-like bHLH-ZIP protein Mlx. This “Extended Myc Network” regulates genes with both common and distinct functions. We have generated hepatocytes lacking Mlx (mlxKO) or Mlx+Myc (double KO or DKO) a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(68 citation statements)
references
References 105 publications
7
61
0
Order By: Relevance
“…A more recent study of Mga function in cancer that expanded upon the above results indicated that CRISPR-mediated Mga inactivation accelerated tumor growth and shortened survival in both the KrasLSL-G12D and KrasLSL-G12D+Tp53-/models of lung cancer [335,337]. While this indicated that Mga loss facilitated the growth of tumors in highly susceptible hosts, it was not determined whether Mga inactivation in otherwise normal mice impacted spontaneous tumor growth as happens with more traditional TSs such as TP53 or Mlx [63,[352][353][354].…”
Section: Mgamentioning
confidence: 99%
See 4 more Smart Citations
“…A more recent study of Mga function in cancer that expanded upon the above results indicated that CRISPR-mediated Mga inactivation accelerated tumor growth and shortened survival in both the KrasLSL-G12D and KrasLSL-G12D+Tp53-/models of lung cancer [335,337]. While this indicated that Mga loss facilitated the growth of tumors in highly susceptible hosts, it was not determined whether Mga inactivation in otherwise normal mice impacted spontaneous tumor growth as happens with more traditional TSs such as TP53 or Mlx [63,[352][353][354].…”
Section: Mgamentioning
confidence: 99%
“…Moreover, ChREBP can also bind to single E-boxes and can do so in a glucose-independent manner [59][60][61]. The fact that Myc can also bind the double Eboxes of the ChoRE suggests that shared gene targets may allow for transcriptional promiscuity and additional levels of cross-talk among members of the Extended Myc Network [63].…”
Section: Chrebpmentioning
confidence: 99%
See 3 more Smart Citations